Management of bifurcation culprit lesion in the setting of anterior ST elevation myocardial infarction. (14th October 2021) - Assal, A; Almaghraby, A; El Amrawy, A
Abstract: Introduction: Coronary bifurcation lesions are considered one of the challenging entities in the field of coronary intervention due to the risk of side branch loss and higher risk of stent thrombosis. However, there is limited data about the proper management of such lesions in the setting of myocardial infarction as most bifurcation lesion studies excluded patients with acute coronary syndrome (ACS). Aim: To compare in-hospital and mid-term outcomes of single-stent and two-stents strategy in the management of bifurcation culprit lesions in patients presenting with anterior STEMI Methods: This retrospective multi-center study included all consecutive patients presented with anterior STEMI who underwent primary PCI between January 2017 and December 2019, coronary angiography showed true bifurcation lesion with sizable side branch that can be managed by stenting. Patients with left main bifurcation lesion, patients indicated for urgent CABG, or patients in cardiogenic shock were excluded. Included patients were divided into two main groups according to the stenting strategy either single or two stents strategy. Six months of follow up data were collected by telephone calls and the examination of medical records Results: Out of 1355 anterior STEMI patients presented between January 2017 and December 2019, 158 patients (11.6%) were identified to have bifurcation culprit lesions with a sizable diagonal branch. The baseline characteristics and angiographic findings were similar in both groups except for higher side branch involvement in the two stents group (83.31%± 11.20 and 71.88%±15.05, t=−5.39, p<0.001). Mean fluoroscopy time (23.96±8.90 vs 17.81±5.72 min) and contrast volume (259.23±59.45 vs 232.58±96.18 ml) were significantly higher in two stents group than single stent group (p=0.049). However the angiographic success rates (residual stenosis ≤30% and restoration of TIMI flow grade II or III) were comparable (96.8% vs 99%, MC p=0.151). There is no significant difference regarding the overall incidence rate of MACCE in both groups 6 months following the index procedure (13.9% vs 16.9%, FEp=0.698), with no difference between different bifurcation stenting techniques in patients managed with two stents Conclusion: Although two stents strategy in the setting of STEMI is much complex with more fluoroscopy time and contrast volume, the procedural success rate and the incidence of complications between two groups were comparable on the medium-term follow up Funding Acknowledgement: Type of funding sources: None.